Policy Analysis and Interventions for HIV AIDS Programs Related to Factors Causing Failed Antiretroviral Treatment in PLWHA at Assolokobal Health Center Jayawijaya Regency - Desi Wenda, Darmawansyah, Sukri, Indar, Stang, Agus Bintara Birawida (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to analyze the policies and interventions of the HIV AIDS program related to the factors causing the failure of antiretroviral treatment in people living with HIV at the Assolokobal Public Health Center, Jayawijaya Regency. This research was conducted in the Assolokobal Community Health Center, Jayawijaya Regency. This type of research is a qualitative research using in-depth interview techniques, observation and document review. There were 7 informants involved in this study. The results of the study show that stigma and culture influence the factors causing ARV failure in PLWHA at the Assolokobal Health Center, knowledge is the cause of ARV failure in PLWHA at the Assolokobal Health Center, Attitudes and Perceptions of PLWHA greatly determine the decision to return for ARV therapy in this study the attitudes and perceptions of PLWHA are still low. In terms of decision making for ARV Return, family and environmental support for PLWHA is quite good, there is a good relationship in terms of communication between officers and PLWHA as well as the availability of adequate facilities at the Assolokobal Health Center, and also the Confidentiality of PLWHA on ARV is strongly influenced by the causal factors of PLWHA themselves and from outside that influence their decision to seek treatment again or to drop out, in other words, ARV failure. Suggestions for this research are that it is hoped that there will be a tiered and continuous provision of information in terms of ARV therapy to PLWHA at the beginning of the visit by the counselor, in this case health workers.